Influences of superfine-grinding and mix enzymatic hydrolysis combined with hydroxypropylation or acetylation on the structure and physicochemical properties of jujube kernel fiber - Zhang, Jiangning; Ye, Zheng (Frontiers in Sustainable Food Systems, 2024)
Introduction Jujube kernel is a low-cost and abundant fiber resource, but its application in food industry is little because of its lower soluble fiber content and poor physicochemical properties. Methods In the current study, jujube kernel fiber (JKF) was modified by three composite methods: superfine-grinding and mix enzymatic hydrolysis alone, and combined with acetylation or hydroxypropylation. Results and discussion After these modifications, the microstructure of JKF became more porous, and its soluble fiber and extractable polyphenol contents, surface area, water adsorption and expansion capacities, and cation exchange capacity were all significantly improved (p < 0.05). Moreover, superfine-grinding and mix enzymatic hydrolysis combined with acetylation treated JKF showed the highest surface hydrophobicity (43.57) and adsorption ability to oil (4.47 g∙g−1). Superfine-grinding, mix enzymatic hydrolysis and hydroxypropylation treated JKF exhibited the largest surface area (142.53 m2∙kg−1), the highest soluble fiber content (17.43 g∙100 g−1), viscosity (14.54 cP), adsorption capacity to glucose (29.61 μmol∙g−1), cation exchange capacity (40.82), and water expansion ability (7.60 mL∙g−1). Therefore, superfine-grinding and mix enzymatic hydrolysis combined with hydroxypropylation or acetylation were both good choice to improve the physicochemical properties of JKF.